Proceedings of 2010 IEEE International Symposium on Circuits and Systems 2010
DOI: 10.1109/iscas.2010.5537729
|View full text |Cite
|
Sign up to set email alerts
|

A heuristic solution to the optimisation of flutter control in compression systems (and to some more binary quadratic programming problems) via ΔΣ modulation circuits

Abstract: An example of how circuit related techniques can help solving optimisatin problems originating from completely different domains is provided. It is shown that a specific class of Unconstrained Binary Quadratic Programming (UBQP) problems, including those arising in the optimisation of flutter control via blade mistuning, can be solved by means of ∆Σ modulators. This is done in steps, first restating the UBQP problem as a specific signal processing problem, and then attacking the latter via the design of a ∆Σ m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…If λ * T j+1 a j = 0, binary values for u * j are determined by Equation (20). When λ * T j+1 a j = 0, the arc is singular, and we may reintroduce constraint (9), u j (1 − u j ) = 0, to force a binary solution.…”
Section: Construct the Lqt Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…If λ * T j+1 a j = 0, binary values for u * j are determined by Equation (20). When λ * T j+1 a j = 0, the arc is singular, and we may reintroduce constraint (9), u j (1 − u j ) = 0, to force a binary solution.…”
Section: Construct the Lqt Problemmentioning
confidence: 99%
“…In [19,20], circuit related techniques are used to transform unconstrained discrete quadratic programming problems and provide high quality suboptimal solutions. Our focus is on problems with linear objective functions, instead of quadratic, and linear equality constraints, instead of unconstrained.…”
Section: Introductionmentioning
confidence: 99%
“…Application to sigma-delta modulation and related electronic systems Sigma-delta (SD also known as delta-sigma) modulation is a technique very widely used throughout electronic systems (Norsworthy et al, 1996). It is first found used as a method of conversion between analogue and digital signals, but the technique is such a useful one that it has found use in many other systems, often well beyond the area of data conversion (Galton et al, 1998;Callegari and Bizzarri, 2010). Because of the simplicity and widespread applicability of the method, we will use the SD modulator and its variants as a vehicle to illustrate many of the methods of the previous section.…”
Section: Discrete-time Dynamicsmentioning
confidence: 99%
“…A/D, D/A and D/D conversion [1,2], frequency synthesis [3], waveform storage [4], signal processing [5] and more. Recently, it has been suggested that they may even be used as heuristic optimizers for special classes of optimization problems [6,7]. In all these applications, their attractiveness mainly derives from the ability to perform noise shaping.…”
Section: Introductionmentioning
confidence: 99%